Reverend Dr. Martin Luther King, Jr. March in Downtown Fresno to Saroyan Theatre - Watkins, Howard::::::::: (1985)
Bruce Morris, Juanita Temple, Betsy Temple and others marching and holding hands Alan Amend wearing beard in middle